‘Feminization’ of physician workforce in Bangladesh, underlying factors and implications for health system: Insights from a mixed-methods study - Hossain, Puspita (PLoS One, 2019)
BACKGROUND: Bangladesh is currently faced with an emerging scenario of increased number of female physicians in the health workforce which has health system implications. For a health system to attract and retain female physicians, information is needed regarding their motivation to choose medical profession, real-life challenges encountered in home and workplaces, propensity to choose a few particular specialties, and factors leading to drop-out from the system. This exploratory mixed-methods study attempted to fill-in this knowledge gap and help the policy makers in designing a gender-sensitive health system. METHODS: Three-hundred and fifteen final year female medical students from four purposively selected medical colleges of Dhaka city (two each from public and private colleges) were included in a quantitative survey using self-administered questionnaire. Besides, 31 in-depth interviews with female students, their parents, and in-service trainee physicians, and two focus group discussions with female students were conducted. Gender disaggregated data of physicians and admitted students were also collected. Data were analysed using Stata version 13 and thematic analysis method, as appropriate. RESULTS: During 2006–2015, the female physicians outnumbered their male peers (52% vs. 48%), which is also supported by student admission data during 2011–2016 from the sampled medical colleges, (67% in private compared to 52% in public). Majority of the female medical graduates specialized in Obstetrics and Gynaecology (96%). Social status (66%), respect for medical profession (91%), image of a ‘noble profession’ (91%), and prospects of helping common people (94%) were common motivating factors for them. Gender disparity in work, career and work environment especially in rural areas, and problems of work-home balance, were a few of the challenges mentioned which forced some of them to drop-out. Also, this scenario conditioned them to crowd into a few selected specialties, thereby constraining health system from delivering needed services. CONCLUSIONS: Increasing number of female physicians in health workforce, outnumbering their male peers, is a fact of life for health system of Bangladesh. It’s high time that policy makers pay attention to this and take appropriate remedial measures so that women can pursue their career in an enabling environment and serve the needs and priorities of the health system.